2018
DOI: 10.1111/nicc.12346
|View full text |Cite
|
Sign up to set email alerts
|

Education on invasive mechanical ventilation involving intensive care nurses: a systematic review

Abstract: Well-designed trials are required to confirm that comprehensive continuing education involving intensive care nurses about mechanical ventilation improves patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 61 publications
(152 reference statements)
0
15
0
7
Order By: Relevance
“…In addition, while most clinical skills within ICUs are closely developed and assessed with education and mentorship (Guilhermino et al, 2018), the study findings demonstrated that PR application was often neglected. Participants reported they had not received formal education or training on PR despite its prevalent use which they equated to general workplace culture and attitudes.…”
Section: Understanding the Ways Of Learningmentioning
confidence: 91%
“…In addition, while most clinical skills within ICUs are closely developed and assessed with education and mentorship (Guilhermino et al, 2018), the study findings demonstrated that PR application was often neglected. Participants reported they had not received formal education or training on PR despite its prevalent use which they equated to general workplace culture and attitudes.…”
Section: Understanding the Ways Of Learningmentioning
confidence: 91%
“…The use of educational module along with the teaching sessions have always been the effective learning strategies to improve knowledge. Globally, several studies have been conducted, which reported that nurses lack adequate knowledge regarding ventilator mechanics (4,(15)(16); and educational modules and various teaching sessions can facilitate in increasing their knowledge and competency (16)(17)(18)(19). The significant difference in pre-test and post-test of the current study revealed that education can be a key to bring a change in the knowledge level.…”
Section: Discussionmentioning
confidence: 65%
“…The research findings in one of the pre-test and post-test studies conducted on 50 nurses in a teaching hospital at Nassiryah City were congruent with the current study findings and reported that nurses had weak knowledge regarding the complication prevention in association with the ventilator mechanics; however, the knowledge scores improved after the application of an educational program (16). Similarly, in a systematic review, 17 of 12 articles including quasi experimental and pre-and postintervention observational design revealed that educational programs for nurses about mechanical ventilation showed statistically significant improvement in patient outcomes including successful weaning trials, increased ventilation compliance, decreased length of intubation and hospital stay, and reduced incidences of VAP (17). Certain demographic variables including highest educational qualification, years of experience in intensive care unit, and designation may also have an effect on participants' knowledge.…”
Section: Discussionmentioning
confidence: 97%
“…No se ha encontrado evidencia específica sobre la relación entre la capacitación en la aspiración de secreciones bronquiales en pacientes intubados y las tasas de NAVM. No obstante, la falta de conocimiento es una barrera en la implementación de las recomendaciones 16 , la literatura muestra que la mejora en la educación y formación de los profesionales en atención directa a pacientes en VM, consigue aumentar significativamente el cumplimiento de los bundles , asociándose a una reducción en la incidencia de la NAVM 17 , 18 , 19 , 20 , 21 , 22 .…”
Section: Medidas Funcionales ( Tabla 2 )unclassified